Fatigue and Its Association With Social Participation, Functioning, and Quality of Life in Systemic Sclerosis. Issue 3 (5th February 2021) - Murphy, Susan L.; Kratz, Anna L.; Whibley, Daniel; Poole, Janet L.; Khanna, Dinesh
Abstract : Objective: Fatigue is consistently ranked as one of the most problematic symptoms of systemic sclerosis (SSc), but the impact of fatigue on daily life is not well characterized. The purpose of this study was to examine the contribution of fatigue to deficits in social participation, functioning, and quality of life. Methods: Baseline data from a sample undertaking a clinical trial were utilized (n = 267). Fatigue, pain interference, depressive symptoms, physical function, and social participation were assessed by measures from the Patient‐Reported Outcomes Measurement Information System. Hierarchical linear regressions were performed to determine the unique contribution of fatigue to social participation, physical function, and quality of life above and beyond the effects of demographic and clinical variables, pain interference, and depressive symptoms. Results: The sample was predominantly female (91%), with an average age of 53.7 years, average disease duration of 9 years, and a mean fatigue T score of 58.7. Of all outcomes, fatigue was most strongly associated with deficits in social participation, explaining 48% of the variance beyond demographic and clinical factors, which is similar to the amount of variance contributed by pain interference and depressive symptoms combined (49%). Fatigue also accounted for significant amounts of variance in physical function and quality of life (R 2 = 0.27 and 0.33, respectively) above and beyond the effects of demographic and clinical factors. Conclusion: Fatigue is an important clinical problem in SSc and is strongly associated with decreased participation in social roles and activities. Rehabilitation interventions that focus on fatigue management may be necessary to maximize participation.